2019
DOI: 10.2217/nnm-2018-0038
|View full text |Cite
|
Sign up to set email alerts
|

Mannosylated Thiolated Paromomycin-Loaded PLGA Nanoparticles for The Oral Therapy of Visceral Leishmaniasis

Abstract: Aim: The present study evaluates the efficacy of paromomycin (PM)-loaded mannosylated thiomeric nanoparticles for the targeted delivery to pathological organs for the oral therapy of visceral leishmaniasis. Materials & methods: Mannosylated thiolated chitosan (MTC)-coated PM-loaded PLGA nanoparticles (MTC-PLGA-PM) were synthesized and evaluated for morphology, drug release, permeation enhancing and antileishmanial potential. Results: MTC-PLGA-PM were spherical in shape with a size of 391.24 ± 6.91 nm and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 36 publications
3
22
0
Order By: Relevance
“…As expected, in vitro macrophage uptake of L. donovani amastigote forms was better for MTC‐PLGA‐PM, with IC 50 0.09 μg/ml, result 36 times lower than the free drug. BALB/c mice treated with MTC‐PLGA‐PM (20 mg/kg) reduced the hepatic parasitic load 3.6 times more than the free drug (Afzal et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…As expected, in vitro macrophage uptake of L. donovani amastigote forms was better for MTC‐PLGA‐PM, with IC 50 0.09 μg/ml, result 36 times lower than the free drug. BALB/c mice treated with MTC‐PLGA‐PM (20 mg/kg) reduced the hepatic parasitic load 3.6 times more than the free drug (Afzal et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…From n values, it can be concluded that it followed (Fickian) diffusion mechanism i.e. gradual swelling of the TCS bandage released the ZnO-NPs via diffusin through polymer matrix [44]. From CS-Alg-ZnO release followed first order release mechanism with a maximum R 2 value of 0.93 and K 1 value of 0.01 [45].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, macrophages are the central host cells which are infected by intracellular pathogens such as Leishmania and Toxoplasma, and it was well-established that mannosylated PM-SLN not only increase the bioavailability of PM, but also mannosylation enhance uptaking PM by macrophages (Frenz et al, 2015). In the study conducted by Afzal et al (2019), the maximum uptake was observed in macrophages that were treated by mannosylated thiolated chitosan-coated PM-loaded PLGA nanoparticles.…”
Section: Discussionmentioning
confidence: 99%
“…This drug faces many challenges, such as quick renal excretion and short half-life in the blood circulation. Indeed, this drug is hydrophilic and has a high molecular weight that makes its uptake difficult (Ghadiri et al, 2012;Afzal et al, 2019). However, PM can be a good option for treatment of parasitic disease due to its safety, low cost, and short course therapy.…”
Section: Introductionmentioning
confidence: 99%